Friction stir processing of aluminium alloy AA7075: Microstructure, surface chemistry and corrosion resistance. (May 2016) - Pang, J.J.; Liu, F.C.; Liu, J.; Tan, M.J.; Blackwood, D.J.
Graphical abstract: Highlights: Aluminium alloy AA7075 friction-stir-processed (FSPed) in both air and water. FSP effect on microstructure and corrosion properties investigated. FSP in air reduces the corrosion rate and increases pitting potential. FSP in water increases the corrosion rate with no effect on the pitting potential. Six-day immersion in 0.5 M NaCl shows reduced corrosion rate for the FSP samples. Abstract: Friction stir process (FSP) was conducted in both air and water on aluminium alloy AA7075, with the latter environment providing the smallest grain size and a higher surface copper level. In 0.5 M NaCl solution, FSP conducted in air was beneficial, reducing the corrosion rate and increasing the pitting potential. When performed in water it was detrimental, having no influence on the pitting potential but increasing the corrosion rate, due to the higher surface area coverage of Cu rich regions increasing the area available for the cathodic reaction. For long-term exposure reduced corrosion rates were observed for both FSP-treated samples.